KONDISI EMOSIONAL YANG BERPACARAN DENGAN YANG TIDAK BERPACARAN SISWA SMP TELEKOMUNIKASI PEKANBARU - Nilam Sari; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is the exixtence of unstable emotions experienced by most teenagers both dating and non-dating. This study aims to find the emosional state of students who are dating and who are not dating. This type of research is descriptive. The population in this study were all students of class VII as much as 2 classes and class VIII as many as 3 classes with a total of 131 students, with a sampling technique that is saturated samples. Conclusions from this study are: 1) the emotional condition of students who are dating generally are often sad and upset because they do not meet girlfriends, are upset because boyfriend are not attentive, do not focus on learning because they are always thinking of boyfriends and shunned by friend since they they have a boyfriend. 2) while the emotional condition of students who are not dating generally feel scared, there is a feeling of fear if there is no opposite sex who likes, jealousy and shame to friends who already have a boyfriend and feel uneasy because they do not have a boy friend.Keywords: Emotional Conditions, Student Intercourse, Student No Relationship